Scientific Literature in Sanskrit - World Sanskrit Conference 2006 : Edinburgh, Scotland); Sarma, Sriramula Rajeswara; Wojtilla, Gyula (Delhi : Motilal Banarsidass Publishers, 2011)
Papers presented at the 13th World Sanskrit Conference, held at Edinburgh during 10-14 July 2006.
Bibliografske bilješke.
Includes verses in Sanskrit
Keywords: sanskrtska književnost; znanstvena literatura